PENGARUH PERILAKU KEPEMIMPINAN TERHADAP PRESTASI KERJA KARYAWAN KOPERASI UNIT DESA (KUD) TANI MAKMUR KECAMATAN KLABANG KABUPATEN BONDOWOSO - Djoko Suhartono; Isadara DP Novitasari (ACTON, 2017)
The low performance of the Village Village Cooperative (KUD) employees prosperous Klabang Sub-district, Bondowoso Regency in carrying out its work duties during this time, have an impact on the low quality and quantity of employee's work in performing its main duty and function. The purpose of this research is to know the behavior of leadership with work performance of KUD Tani Makmur. This type of research uses a quantitative research approach with a sample of 21 respondents. Based on the results of regression analysis known that the independent variable (leadership behavior) has a significant influence on the dependent variable (employee performance).